Efficient traffic information dissemination algorithm based on ranking - ZHONG Ting; QIN Zhi-guang (Tongxin xuebao)
An efficient algorithm was proposed for disseminating real-time traffic information in vehicular ad-hoc networks （VANET’s）. In this algorithm, each participating vehicle made local decision on when to disseminate and how many to disseminate by local traffic information. In order to deal with the bandwidth and memory constraints, reports were prioritized in terms of their importance ranks. Finally, the proposed algorithm was compared by simulations with Grassroots, an existing VANET flooding dissemination algorithm. The simulation results show that the algorithm is better than Grassroots.